steganography in colored images based on biometrics - Zeena Nabeel Jameel AL-Kateeb; Marriam Raad Jasim Mohammed AL-Bazaz (Tikrit Journal of Pure Science)
Due to the great significance of the concealment and transfer of confidential data and the many and varied algorithms presented in this field, as well as the big and rapid development of the use of biometrics in the issues of reliability and verification of the identity of people in support of information security. Therefore this research has provided a suggested algorithm to hide confidential data in colorful images based on the features of engineering dimensions of the human hand as one of the types of biometrics; we extracted a set of these characteristics and processed them to build a matrix that specifies the map of the distribution of confidential data in the cover image. The proposed method was applied to a set of images to hide a set of confidential messages and the visual quality of the cover image was not affected after the concealment. The practical results explain the efficiency of this method was measured in terms of comparison between the original image before and after concealment. The performance of the algorithm and the method of its application were measured using measures of efficiency of the work, whereas the Peak Signal Noise Ratio was used, the highest ratio obtained was 81.3417, and Mean Square Error was approximately 0.0008 as a maximum limit, while the error rate was the restored confidential message after hiding Bit Error Rate = 0 in all cases